Forming Children's Independent Character through the Habituation Method in Group A Paud Satya Prawira in Academic Year 2021/2022 - Septiani, Devi; Hadi, Rusman (Lembaga Penelitian dan Pendidikan Mandala, 2024)
This study aims to describe efforts to shape children's independent character at Satya Prawira PAUD in the 2021/2022 academic year. This research focuses more on how to increase the independent character of children at the age of 4-5 years. This research is a Classroom Action Research (PTK) where the subjects in this study are group A students from PAUD Satya Prawira with a total of 10 students. The focus of this research is the independent character of children at the age of 4-5 years. In this study, researchers used a habituation method in the form of giving examples and an action that can help children's independent character to increase according to the criteria desired by the researcher. In this study for data collection only used two cycles, in which cycle I the level of children's independence was still low because there were still some children's independence had not increased significantly. In cycle I with the results of Developing as Expected (BSH) there were 3 children or equivalent to 30%, and Developing Very Well (BSB) consisted of 7 children or equivalent to 70%. In addition, there is also a cycle II as a planning improvement action which from cycle I to cycle II has increased by 10% so that children who are Developing as Expected (BSH) consist of 2 children or equivalent to 20%, and Developing Very Well (BSB) totaling 8 children or equivalent to 80%. So, with this increase, the researcher stopped his research because the researcher had obtained the right results according to the desired classical value. However, the individual scores are still less than perfect and there are still children who are below the assessment criteria.